Structure and characteristics of community‐based multidisciplinary wound care teams in Ontario: An environmental scan. Issue 1 (13th February 2015) - Abrahamyan, Lusine; Wong, Josephine; Pham, Ba'; Trubiani, Gina; Carcone, Steven; Mitsakakis, Nicholas; Rosen, Laura; Rac, Valeria E.; Krahn, Murray
Abstract Multidisciplinary team approach is an essential component of evidence‐based wound management in the community. The objective of this study was to identify and describe community‐based multidisciplinary wound care teams in Ontario. For the study, a working definition of a multidisciplinary wound care team was developed, and a two‐phase field evaluation was conducted. In phase I, a systematic survey with three search strategies (environmental scan) was conducted to identify all multidisciplinary wound care teams in Ontario. In phase II, the team leads were surveyed about the service models of the teams. We identified 49 wound care teams in Ontario. The highest ratio of Ontario seniors to wound team within each Ontario health planning region was 82, 358:1; the lowest ratio was 14, 151:1. Forty‐four teams (90%) participated in the survey. The majority of teams existed for at least 5 years, were established as hospital outpatient clinics, and served patients with chronic wounds. Teams were heterogeneous in on‐site capacity of specialized diagnostic testing and wound treatment, team size, and patient volume. Seventy‐seven percent of teams had members from three or more disciplines. Several teams lacked essential disciplines. More research is needed to identify optimal service models leading to improved patient outcomes.